Student experiences of two small group learning‐teaching formats: Seminar and fishbowl. (21st January 2019) - Tricio, Jorge; Montt, Juan; Orsini, Cesar; Gracia, Benjamín; Pampin, Francisco; Quinteros, Camilo; Salas, Macarena; Soto, Reinaldo; Fuentes, Nelson
Abstract: Introduction: As teaching strategies, the seminar and fishbowl approaches promote active learning and shift the focus from the teacher to the learner. The aim of this study was to compare the self‐reported perceptions of each student‐centred teaching technique amongst a group of dental students as well as resultant quiz scores after each teaching technique. Material and Methods: During the first semester of 2017, all year‐3 (N = 88) Semiology and year‐5 (N = 71) Oral Surgery students participated in weekly seminars in which teams of students from both cohorts were given an actual clinical case to study; a diagnosis and treatment plan would be rendered, and an oral case presentation would be presented to the rest of the class. In the second semester, the same students tried to solve similar clinical cases using the fishbowl training format. A course coordinator provided final feedback, and the session culminated with a quiz. Students were invited to provide quantitative and qualitative perceptions whilst quiz scores obtained during seminar and fishbowl teaching formats were compared. Results and Discussion: A total of 97 (61%) seminar and 92 (58%) fishbowl students provided insights regarding these teaching techniques. Both cohorts believed the fishbowl format allowed them to be actively involved. However, only year‐3 students gave the fishbowl format a significantly higher score than the seminar format, considering it an attractive format that allowed them to learn. In contrast, year‐5 students believed the seminars met their expectations better than the fishbowl format. Interesting clinical cases as well as the final round of feedback were qualitative themes reported by both cohorts. The mean seminar and fishbowl quiz scores were statistically significant different for year‐3 students ( P < 0.0001), but not for year‐5 students ( P = 0.09). Conclusions: These findings suggest that a more structured small‐group learning‐teaching format can be implemented for younger students whilst at the same time allowing more flexible organisation for senior students.